The Role of Human Resources Strategy in Achieving Professional Growth in Private Universities Considering Vision 2030 - Jaghoubi, Salma Mohammed; Owayyid, Sarah Abdullah (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to identify the reality of applying the human resources strategy and its role in achieving professional growth in private universities in the city of Riyadh and the impact of its application on administrative staff in the light of Vision 2030. The study adopted the descriptive analytical approach. To collect data, the questionnaire tool was designed and distributed to a random sample of (100) administrative staff in private universities. The results indicated the application of strategic planning for human resources in the light of Vision 2030 in private universities in Riyadh. Moreover, the study found a statistically significant positive relationship between human resources strategies and their sub-dimensions represented in (strategic planning for human resources in light of Vision 2030 - training and development strategy - compensation strategy - participation of senior and executive management in human resources strategies) and professional growth among administrative staff in private universities in the Kingdom in Riyadh. The results also showed that there are no significant differences between the average ranks of the responses of the study sample members on the reality of the application of the human resources strategy in private universities in the Kingdom in the Riyadh region, as well as the level of professional growth among administrative staff in private universities according to the variable in the job title.  While it turned out that there are statistically significant differences at the level of (0.05) between the averages in the ranks of the answer members of the study sample on the level of professional growth among administrative employees in private universities in Riyadh according to the variable of the employer, in favor of the members of the study sample at the Arab Open University. The study recommended conducting research and studies on the reality of applying the human resources strategy to administrative staff by applying it to other universities. The study also recommended conducting studies dealing with obstacles, methods of activating strategies, and its impact on improving the quality of their work life.
Keywords: human resources strategy; human resources; professional growth; administrative staff